O negro na missa: tramas interculturais no álbum Missa dos quilombos de Milton Nascimento - Braga, Pedro Paulo de Freitas (2014)
This dissertation is mainly about the album Missa dos Quilombos (1982) by Milton Nascimento. Our approach seeks to establish an interdisciplinary dialogue between the cultural studies and musicology, dealing with music in its musical and extra-musical characteristics. In this study, the black popular music reveals its central value. It suggests the preservation of diffuse cultural patterns of memory, which are rescued and historically reinterpreted in the black Brazilian daily life. The practices of african-Brazilian culture, which was denied and chased from the slavery days until nowadays, occupied through Theology of Liberation (on a temporary basis, but effective) their space within Church. In Missa dos Quilombos, a system of rules is set while listening to the music, whose symbolic dimension gives a symbolic character, reconnecting with the culture and past of the black people. During this work, we noticed how Missa dos Quilombos is complex. The set of elements that it’s composed is a endless universe of cultural exchange, or Brazilian history knowledge. They help us to know, think and question the past and present, as well as the methods used to solve it. This perspective allowed us to have a dialogue with practices and representations that show the participation of social actors involved in the album.